The influence of physical activity on the health and treatment of schizophrenia patients - Katarzyna Kuśmierczyk; Marta Jurga; Patrycja Karkos; Marta Kras; Bartłomiej Gastoł; Karolina Mikołap; Arkadiusz Staroń; Michał Ciołkosz; Elena Sztemberg; Filip Grajnert (Nicolaus Copernicus University in Toruń, 2024)
Schizophrenia is a chronic and severe mental illness that affects multiple areas of life. Patients with schizophrenia are prone to developing serious and even fatal disorders when it comes to their physical health. They have a higher mortality risk and an average of 14,5 years of potential life lost compared to the general population. Physical activity decreases mortality, reduces cardiovascular risk, and improves mental health. Within this article, we explore the topic of physical activity and its influence on the physical and mental health of schizophrenia patients and their treatment.